2013
DOI: 10.1007/s00167-013-2772-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of arthroscopic treatment for displaced lateral clavicle fractures using a double button device

Abstract: Purpose The purpose of this study was to assess the clinical and radiological outcomes of an arthroscopically assisted fixation of type IIB fractures using a double button device. Methods Twenty‐one patients with a type IIB displaced fracture of the clavicle who received an arthroscopically assisted fixation using a double button device were enrolled from 2009 to 2011. Clinical assessment included the patient's demographics, cause of injury, delay before surgery, time for surgery, time before resuming work and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 34 publications
3
62
0
3
Order By: Relevance
“…Numerous complications in relation to arthroscopic fixation have been mentioned in the literature, including implant failure with nonunion, transient adhesive capsulitis, symptomatic AC joint arthritis, coracoid fracture, and clavicular erosion. 12,13,16,21) However, we did not encounter any of them except instability and over reduction. Even though Loriaut et al 13) and Motta et al 14) reported satisfactory radiologic outcomes after arthroscopic stabilization based on plane radiographs, malreduction/posterior angulation, an occult complication and its effect on clinical outcome has never been mentioned previously as it is not evident on routine Xrays.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Numerous complications in relation to arthroscopic fixation have been mentioned in the literature, including implant failure with nonunion, transient adhesive capsulitis, symptomatic AC joint arthritis, coracoid fracture, and clavicular erosion. 12,13,16,21) However, we did not encounter any of them except instability and over reduction. Even though Loriaut et al 13) and Motta et al 14) reported satisfactory radiologic outcomes after arthroscopic stabilization based on plane radiographs, malreduction/posterior angulation, an occult complication and its effect on clinical outcome has never been mentioned previously as it is not evident on routine Xrays.…”
Section: Discussionmentioning
confidence: 69%
“…12,13,16,21) However, we did not encounter any of them except instability and over reduction. Even though Loriaut et al 13) and Motta et al 14) reported satisfactory radiologic outcomes after arthroscopic stabilization based on plane radiographs, malreduction/posterior angulation, an occult complication and its effect on clinical outcome has never been mentioned previously as it is not evident on routine Xrays. Rieser et al, 22) in a biomechanical evaluation, showed that combination of a locking plate and tightrope was superior to either method alone as a result of greater construct strength and stiffness.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations